A Study on the Legal Issues of Music Copyright in Korea and Japan - Lim, Myeong Seob; Kim, Kyounghee (Advances in Social Sciences Research Journal, 2018)
Copyright is an essential right of the creator and an important element of the culture creation industry. However, it is a misconception that the copyrighted property is the property of the copyright owner and that the copyright law protects the rights of the copyright owner only. Because the ultimate goal of copyright is to improve and develop the cultural industry. For the development of the cultural industry, it is very important for the producers who make the contents or those who commercialize the contents to understand the copyright. In this study, we will propose a promotion method of the music industry by examining the problem by investigating cases of collection of copyright fees, collecting regulations, and related copyright laws of both Korea and Japan.